Agency detection in predictive minds - Andersen, Marc,Schjødt, Uffe,Müller, Sebastian,Pfeiffer, Thies (Enthalten in:Religion, brain & behavior;London [u.a.] : Routledge, 2011;9(2019), 1, Seite 52-64;Online-Ressource, 2019)
Since its inception, explaining the cognitive foundations governing sensory experiences of supernatural agents has been a central topic in the cognitive science of religion. Following recent developments in perceptual psychology, this pre-registered study examines the effects of expectations and sensory reliability on agency detection. Participants were instructed to detect beings in a virtual forest. Results reveal that participants expecting a high probability of encountering an agent in the forest are much more likely to make false detections than participants expecting a low probability of such encounters. Furthermore, low sensory reliability increases the false detection rate compared to high sensory reliability, but this effect is much smaller than the effect of expectations. While previous accounts of agency detection have speculated that false detections of agents may give rise to or strengthen religious beliefs, our results suggest that the reverse direction of causality may also be true. Religious teachings may first produce expectations in believers, which in turn elicit false detections of agents. These experiences may subsequently work to confirm the teachings and narratives upon which the values of a given culture are built.
10.1080/2153599X.2017.1378709
Keywords: Agency Detection; HADD; cognitive science of religion; perception; predictive processing; religious teachings; virtual reality